2015
DOI: 10.1098/rsob.150209
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of Plk4 induces centrosome amplification, loss of primary cilia and associated tissue hyperplasia in the mouse

Abstract: To address the long-known relationship between supernumerary centrosomes and cancer, we have generated a transgenic mouse that permits inducible expression of the master regulator of centriole duplication, Polo-like-kinase-4 (Plk4). Over-expression of Plk4 from this transgene advances the onset of tumour formation that occurs in the absence of the tumour suppressor p53. Plk4 over-expression also leads to hyperproliferation of cells in the pancreas and skin that is enhanced in a p53 null background. Pancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
148
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(170 citation statements)
references
References 76 publications
10
148
2
1
Order By: Relevance
“…STIL levels are tightly regulated during the cell cycle: the protein level is very low in G1 phase, increases gradually during and after the G1-S transition, and finally starts declining at the time of metaphase-anaphase transition [Arquint et al, 2012]. While depletion of STIL in human cells blocks centriole duplication, overexpression of the protein results in the formation of multiple daughter centrioles around a single mother centriole [Kitagawa et al, 2011;Tang et al, 2011;Arquint et al, 2012;Arquint and Nigg, 2014], a phenotype reminiscent of those observed for both hsSAS-6 and PLK4 overexpression [Habedanck et al, 2005;Leidel et al, 2005;Kleylein-Sohn et al, 2007;Peel et al, 2007;Rodrigues-Martins et al, 2007;Strnad et al, 2007;Cunha-Ferreira et al, 2009;Rogers et al, 2009;Marthiens et al, 2013;Coelho et al, 2015]. Interestingly, mutations in PLK4 have been associated with primordial dwarfism and retinopathy/chorioretinopathy, thus extending the clinical spectrum correlated to centriole de- fects [Martin et al, 2014;Shaheen et al, 2014;Tsutsumi et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…STIL levels are tightly regulated during the cell cycle: the protein level is very low in G1 phase, increases gradually during and after the G1-S transition, and finally starts declining at the time of metaphase-anaphase transition [Arquint et al, 2012]. While depletion of STIL in human cells blocks centriole duplication, overexpression of the protein results in the formation of multiple daughter centrioles around a single mother centriole [Kitagawa et al, 2011;Tang et al, 2011;Arquint et al, 2012;Arquint and Nigg, 2014], a phenotype reminiscent of those observed for both hsSAS-6 and PLK4 overexpression [Habedanck et al, 2005;Leidel et al, 2005;Kleylein-Sohn et al, 2007;Peel et al, 2007;Rodrigues-Martins et al, 2007;Strnad et al, 2007;Cunha-Ferreira et al, 2009;Rogers et al, 2009;Marthiens et al, 2013;Coelho et al, 2015]. Interestingly, mutations in PLK4 have been associated with primordial dwarfism and retinopathy/chorioretinopathy, thus extending the clinical spectrum correlated to centriole de- fects [Martin et al, 2014;Shaheen et al, 2014;Tsutsumi et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, centrosome amplification did accelerate tumorigenesis in a p53-deficient skin epidermis 157 . Moreover, global PLK4 overexpression also accelerated the onset of lymphomas and sarcomas in p53 null mice and promoted hyperproliferation in the skin and pancreas 158 . Taken together, these studies validate a central role of p53 in restricting the continued proliferation of cells with centrosome amplification in mammals 107 .…”
Section: Centrosome Defects and Cancermentioning
confidence: 94%
“…Conceivably, the induction of centrosome amplification in mouse models can suffice to accelerate cancer onset in the absence of p53 (Coelho et al 2015;Serçin et al 2016), but evidence for the lack of such an effect also exists Vitre et al 2015). This apparent controversy suggests that the oncogenic potential of extra centrosomes may vary depending on context or cell type, but all studies agree that tissues retaining functional p53 are nonpermissive to propagate supernumerary centrosomes (Coelho et al 2015;Kulukian et al 2015;Vitre et al 2015;Serçin et al 2016). Perturbations of the centrosome duplication cycle lead to p53 stabilization and p53-dependent cell cycle arrest (Holland et al 2012;Lambrus et al 2015;Wong et al 2015).…”
mentioning
confidence: 95%
“…While extra centrosomes can be causative of chromosomal instability (CIN) by promoting merotelic kinetochoremicrotubule attachments in mitosis (Ganem et al 2009;Silkworth et al 2009), they may promote oncogenesis in additional ways unrelated to CIN; e.g., by increasing Rac1 activity that facilitates invasive cellular behavior (Godinho et al 2014). Conceivably, the induction of centrosome amplification in mouse models can suffice to accelerate cancer onset in the absence of p53 (Coelho et al 2015;Serçin et al 2016), but evidence for the lack of such an effect also exists Vitre et al 2015). This apparent controversy suggests that the oncogenic potential of extra centrosomes may vary depending on context or cell type, but all studies agree that tissues retaining functional p53 are nonpermissive to propagate supernumerary centrosomes (Coelho et al 2015;Kulukian et al 2015;Vitre et al 2015;Serçin et al 2016).…”
mentioning
confidence: 99%